Gamificação na perspectiva educação especial inclusiva: contribuições de uma formação docente para o ensino de ciências - Coelho, Caroline Pugliero (2025)
The thesis investigates how teacher training with gamified features can contribute to promoting inclusive science teaching, especially for students with disabilities. The study covers four main axes: analysis of legislative documents on inclusive educational policies, systematic literature review on gamification in inclusive special education, investigation of science teachers’ perceptions of inclusive education challenges for students with disabilities, and the development and implementation of gamified teacher training courses. The results show that gamification is a powerful methodological strategy for inclusive science teaching, enhancing motivation, autonomy, and engagement among teachers and students, and facilitating the development of personalized, context-relevant pedagogical practices. The study also highlights the importance of ongoing, context-based teacher training to consolidate inclusive school practices.